Contact detection approach between wheel and rail surfaces - Marques, Filipe (2020)
This work presents a general formulation to identify the contact points for the interaction between wheels and rails in the context of railway dynamics simulations. This formulation treats the wheel and rail as parametric surfaces and searches the contact between each wheel strip and the rail independently to avoid the numerical difficulties due to the wheel concave zone. This methodology assumes the rail as locally straight and takes advantage that its potential contacting surface is always convex. For the evaluation of contact forces, two Hertzian-based models are employed for normal and creep forces. A trailer vehicle running on a curved track is used to demonstrate the effectiveness of this methodology.